Predictors of breast feeding self-efficacy in the immediate postpartum period: A cross-sectional study. (October 2016) - Yang, Xiao; Gao, Ling-ling; Ip, Wan-Yim; Sally Chan, Wai Chi
Abstract: Objective: to examine breast feeding self-efficacy and identify its predictors among mainland Chinese mothers in the early postpartum period. Design and setting: a cross-sectional descriptive questionnaire survey was conducted in a regional teaching hospital with childbirth rate over 3000 per year at Guangzhou, China from April 1 to July 14, 2014. Participants: a total of 571 Chinese mothers who were within 72–96 hours post partum were recruited consecutively to the study. Measurements: data were collected by the Chinese version of the Breastfeeding Self-efficacy Scale-Short Form (BSES-SF), the Network Support for Breastfeeding Scale (NSBS) and a socio-demographic data sheet. Findings: a total of 640 eligible women was approached and 571 mothers completed the study with the response rate of 89%. Mothers reported moderate level of breast feeding self-efficacy in the immediate postpartum period. The best-fit regression analysis revealed six variables that explained 43.9% of the variance in breast feeding self-efficacy in the immediate postpartum period. They were intention of breast feeding, support from husband, support from nurses/midwives, attending antenatal breast feeding classes, time from childbirth to initiate breast feeding and previous breast feeding experience. Conclusions and implications for practice: this study found six predictors of breast feeding self-efficacy in the immediate postpartum period. In order to increase maternal breast feeding self-efficacy level, a more women-centred approach is recommended. Mothers and fathers should be facilitated to attend antenatal classes on breast feeding. New mother' husband could be encouraged in supporting breast feeding. Nurses and midwives could encourage new mothers to initiate breast feeding as soon as possible. Further work to promote early mother–infant contact post birth, such as via skin to skin contact should also be facilitated where possible. Highlights: Chinese mothers reported moderate level of breast feeding self-efficacy. Intention of breast feeding was a predictor of breast feeding self-efficacy. Attending antenatal classes was a predictor of breast feeding self-efficacy. Time of breast feeding initiation was a predictor of breast feeding self-efficacy.